Rib impingement in first class cricketers: case reports of two patients who underwent rib resection. Issue 8 (21st June 2006) - Boyce Cam, N J; Muthukumar, N; Boyle, S; Lawton, J O
Abstract : Two first class cricket bowlers presented with costoiliac pain secondary to rib impingement. In both patients, conservative management of the injury had failed to improve symptoms. Surgical resection of the affected rib was undertaken. At follow up, both patients had made a good recovery and had returned to competitive cricket.